2001
DOI: 10.29044/v5i2p66
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Analysis Psychotherapy for a Case of Mixed Anxiety & Depression: A Pragmatic Adjudicated Case Study – ‘Alastair’

Abstract: Using an original method of case evaluation which involved an analysis panel of over 80 Italian psychologists and included a lay case evaluation, the author has investigated the effectiveness of transactional analysis psychotherapy for a case of mixed anxiety and depression with a 39 year old white British male who attended 14 weekly sessions. , within an overall adjudicational case study method. The conclusion of the analysis panel and the lay judge was unanimously that this was a good outcome case and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…A few months after that, he provided yet another case (Widdowson 2013) and a year after that the fifth case appeared (Widdowson 2014), based on a case of mixed anxiety and depression.…”
Section: Editorial Julie Haymentioning
confidence: 99%
“…A few months after that, he provided yet another case (Widdowson 2013) and a year after that the fifth case appeared (Widdowson 2014), based on a case of mixed anxiety and depression.…”
Section: Editorial Julie Haymentioning
confidence: 99%
“…Systematic case study research has already been applied to investigate the effectiveness of TA for people with long term health conditions (McLeod, 2013a;2013b) and HSCED methodology has been successfully applied to TA and widely described in this Journal by Widdowson (2012a). Recently, several HSCEDs supporting the effectiveness of TA treatment for depression (Widdowson, 2012a(Widdowson, , 2012b(Widdowson, , 2012c(Widdowson, , 2013Benelli et al, 2016aBenelli et al, , 2016bBenelli et al, , 2016c have been published, as was an additional adjudicated study, which demonstrated effectiveness of TA for mixed depression and anxiety (Widdowson, 2014). Furthermore, a related study was published on TA for emetophobia (Kerr, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several HSCEDs supporting the effectiveness of TA treatment for depression (Widdowson, 2012a(Widdowson, , 2012b(Widdowson, , 2012c(Widdowson, , 2013Benelli, 2016aBenelli, , 2016bBenelli, , 2016c have been published, as was an additional adjudicated study which demonstrated effectiveness of TA for mixed depression and anxiety (Widdowson, 2014). Furthermore, a related study was published on TA for emetophobia (Kerr, 2013).…”
Section: Introductionmentioning
confidence: 99%